Profit Sharing System in Bugis Agriculture: Ethnographic Study in South Sulawesi - Feby Triadi Triadi (JURNAP: Jurnal Administrasi Publik, 2025)
The profit sharing system is a traditional mechanism that influences the economic and social structure of Bugis agriculture, especially in income distribution, relationships between farmers, and management of production risks. This research uses a qualitative ethnographic approach to explore farmers' practices, perceptions and strategies in dealing with the profit sharing system. Data was collected through in-depth interviews with farmers and capital owners, participatory observation on agricultural land, and analysis of local documentation related to production sharing agreements. Thematic analysis was carried out to identify decision-making patterns, profit sharing mechanisms, and farmers' adaptation to production risks and uncertainties. The research results show that the success of a profit-sharing system depends on transparency, social agreement, and community negotiation skills, where farmers actively adjust production and profit-sharing strategies to make them fair and sustainable. This study emphasizes the importance of the profit sharing system as a means of risk management, preserving traditions, and economic empowerment of the Bugis agricultural community.